Permasalahan Reintegrasi Sosial Mantan Narapidana Pembunuhan Dalam Perspektif Labelling Theory dan Reintegrative Shaming (Studi Kasus Komplek Perumahan X Daerah Jakarta Selatan) - Christabel, Odelia Talitakum; Srihadiati, Triny (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Social stigma against former inmates often becomes a major obstacle in the process of social reintegration, particularly in cases involving serious crimes such as murder. This study aims to explore how the labelling process by society creates barriers to the reintegration of ex-convicts who have served sentences for murder. Using a qualitative case study approach involving one former convict and six community informants, this research identifies patterns of social interaction that reveal both formal and informal labelling practices and their impact on identity reconstruction and social participation. The findings show that social labelling not only leads to exclusion but also contributes to the development of a negative self-image that hinders the reformation of identity. The labelling process tends to be progressive, creating a recurring cycle of stigma. However, the study also highlights the role of community leaders who apply reintegrative shaming strategies—condemning the act without rejecting the individual—which provide a more constructive and inclusive space for social recovery. This study recommends the active involvement of community actors and a community-based approach in supporting social reintegration, emphasizing the need to distinguish between a person's past actions and their potential for change. The findings underscore the importance of shifting from stigmatizing practices toward restorative reintegration in Indonesia’s social and correctional policies. This study enriches the criminological discourse in Indonesia by emphasizing the importance of the social dimension in the successful reintegration of former correctional officers.